Dias de Marvila - Falanga, Roberto (2020)
Os Dias de Marvila” (hereafter ODM) is a cultural programme organized by Municipal Library of Marvila that seeks to promote socio-territorial cohesion and combat social stigma associated to the Marvila neighbourhood. Towards this aim, ODM approaches residents and citizens at large as potential agents of culture and change. The programme is implemented with local residents, associations, public institutions, together with artists and cultural organisations. ODM started in 2017 in a partnership with the Maria Matos Municipal Theatre that is located in Alvalade, a neighbourood close, although separated from Marvila due to the many urban barriers (such as the railways and highways) that characterise the ROCK area in Lisbon. In 2017 the aim of the programme was to bridge the two areas by offering multiple cultural initiatives in Marvila and Alvalade. In 2018, the second edition of ODM was concentrated in the Marvila area, with initiatives in the city center aimed at disseminating the programme outside Marvila, and attract new public. The second edition was supported by the ROCK project and by the Municipality of Lisbon. It integrated a wide range of initiatives around six main topics: theatre, art, performance, music, exhibitions, conferences, and guided tours